Bioabsorbable Steroid Eluting Stents in the Treatment of Recurrent Rathke's Cleft Cyst - Ference, Elisabeth H.; Badran, Karam W.; Kuan, Edward C.; Bergsneider, Marvin; Heaney, Anthony P.; Wang, Marilene B. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives Bioabsorbable steroid eluting stents may prevent the stenosis of ostia after sinus surgery. We describe a technique utilizing this technology to prevent the reformation of Rathke's cleft cysts (RCC) after transnasal transsphenoidal surgical drainage.Design This study is based on retrospective review.Setting The research took place at Tertiary academic medical center.Participants Patients who underwent endoscopic marsupialization of RCC with stent placement were participated in this study.Main Outcome Measures Demographics, surgical history, outcomes, and complications were primary measures of this study.Results Four patients underwent drainage of a recurrent RCC with subsequent stent placement. All patients consented to off-label use of the stent. The mean age of patients was 42 years old and the number of prior drainage procedures ranged from 1 to 3. The stent was placed directly into the opening of the cyst after drainage with no other tissue placed into the cyst cavity or opening. The stents are bioabsorbable and were not removed after surgery but were evaluated endoscopically at 2 and 6 weeks after surgery. The patients have been followed for a mean of 14 months after surgery with no evidence of recurrence on endoscopic exam or imaging. No patient had cerebrospinal fluid leak during or after the operation or permanent endocrinopathy.Conclusion The use of a bioabsorbable steroid eluting stent had no unanticipated consequences and all drainage pathways of all the RCCs remain patent. The use of this technology may decrease recurrence rates in revision or complex cases where patients have extensive scarring of the operative field from prior drainage procedures. Further follow-up of the current cases and study in a larger cohort are warranted.
Keywords: Rathke's cleft cyst; stent placement; skull base; steroid eluting stents; recurrence